Electrophysiological properties of melanin-concentrating hormone neuron subpopulations defined by anatomical localization and CART expression - Adekunle, Rafiat Damilola; Chowdhury, Mohammed Sohel; Fang, Lisa Z.; Hirasawa, Michiru (Frontiers in Cellular Neuroscience, 2025)
IntroductionMelanin-concentrating hormone (MCH) neurons are essential regulators of energy and glucose homeostasis, sleep–wake behaviors, motivation, learning and memory. These neurons are anatomically distributed across the medial (MH) and lateral hypothalamus (LH), and the adjacent zona incerta (ZI), which may represent functional subgroups with distinct connectivity with different brain regions. Furthermore, MCH neurons can be classified according to co-expression of neuropeptides, such as cocaine and amphetamine- regulated transcript (CART).MethodsTo identify functional similarities and differences of MCH subpopulations, we characterized their intrinsic electrophysiological properties using whole cell current clamp recording on acute brain slices from male and female mice.ResultsMCH neurons were classified into subgroups according to their anatomical localization in three MCH-rich brain areas: MH, LH and ZI. Among the three brain regions, ZI MCH neurons were the least excitable while LH MCH neurons were the most excitable. Furthermore, grouping MCH neurons according to CART co-expression revealed that MCH/CART− cells are uniquely depolarized and excitable, and display H-currents. These MCH/CART− cells were mainly found in the LH, which may in part explain why LH MCH neurons are more excitable. While some sex differences were found, the majority of parameters investigated were not different.DiscussionOur results suggest that MCH/CART− cells are electrophysiologically distinct, whereas MCH/CART+ cells are largely similar despite their diffuse distribution in the hypothalamus. It is therefore a combination of intrinsic electrophysiological properties and neurochemical identities, in addition to anatomy and connectivity that are likely to be critical in defining functional subpopulations of MCH neurons.